Learning Technology to Improve the Absorption of Islamic Religious Education in Elementary Schools: Teknologi Pembelajaran untuk Meningkatkan Daya Serap Pendidikan Agama Islam di Sekolah Dasar - Hidayat, Rahmat; Mappanyompa; Ali, Mustapa (Halaqa: Islamic Education Journal, 2025)
General Background: Learning technology has become a pivotal tool in enhancing educational quality, particularly in the digital era. Specific Background: In Islamic Religious Education (PAI), the shift from conventional methods to digital learning tools such as videos and PowerPoint presentations promises more interactive and meaningful instruction. Knowledge Gap: However, studies evaluating the effectiveness and inclusiveness of learning technologies in elementary-level Islamic education remain limited, especially for diverse student needs and under-resourced schools. Aims: This study investigates the urgency and effectiveness of learning technology in improving elementary students' absorption of Islamic Religious Education materials. Results: Using a qualitative case study at SD Negeri 3 Kekait, findings show that digital media improves student engagement and understanding of abstract spiritual values, although limitations in teacher digital skills and support for students with special needs persist. Novelty: The study highlights the integration of spiritual values through visual media and emphasizes adaptive strategies for inclusivity, offering fresh insights into character education in religious contexts. Implications: These results suggest the necessity for professional development and infrastructure support to maximize the pedagogical potential of digital technology, ultimately contributing to the formation of students' moral character and improving Islamic education in the digital age.Highlight : Learning technology (videos, PowerPoint) increases student engagement and understanding in Islamic Religious Education at the elementary level. Barriers include limited teacher digital skills and infrastructure challenges in schools. Technology helps internalize spiritual values through visual storytelling, enhancing character education. Keywords : Learning Technology, Student Absorption, Islamic Religious Education, Digital Media, Elementary School